Critical Reading from Socially Relevant Problems - Romero-Olarte, Betty; Ramírez-Rojas, María Isabel (Universidad Pedagógica y Tecnológica de Colombia, 2020)
This document presents a classroom experience with the purpose to develop critical reading level in eleventh grade students, through a teaching unit in the area of Political Science and Economics, through socially relevant problems. The work was done under the qualitative descriptive approach and the sample was formed by 20 students of the eleventh grade from Colegio Nuestra Señora de la Concepción. The initial instrument showed that most of the students present difficulties in the critical reading level since, in the contextual reading, they only have an approach to the explanation of the sociocultural character of the text; at the inferential reading, they they show difficulties, because they focus on the relationship with their previous knowledge and they do not go beyond the text. At the intertextual reading, they present an absence of it, because their reasoning only presents evocations of established facts from their cultural knowledge and everyday life, they do not go beyond what the author says. The classroom performed a didactic unit in which four sequences were proposed. These sequences intend to develop critical reading. They included continuous and discontinuous texts, in which some socially relevant problems were approached. After the intervention, students achieved a moderate progress in some of the skills of contextual reading and inferential reading, but, at intertextual reading, the students achieved a slight progress.  On the other hand, the work shows that the implementation of texts about socially relevant problems articulated to academic contents of different areas, generates a high degree of motivation in students.